Prospective Long-Term Cohort Study of Subjects With First-Episode Psychosis Examining Eight Major Outcome Domains and Their Predictors: Study Protocol - Peralta, Victor; Moreno-Izco, Lucía; García de Jalón, Elena; Sánchez-Torres, Ana M.; Janda, Lucía; Peralta, David; Fañanás, Lourdes; Cuesta, Manuel J.; , SEGPEPs Group (Frontiers in Psychiatry, 2021)
Background: Our current ability to predict the long-term course and outcome of subjects with a first episode of psychosis (FEP) is limited. To improve our understanding of the long-term outcomes of psychotic disorders and their determinants, we designed a follow-up study using a well-characterized sample of FEP and a multidimensional approach to the outcomes. The main goals were to characterize the long-term outcomes of psychotic disorders from a multidimensional perspective, to address the commonalities and differential characteristics of the outcomes, and to examine the common and specific predictors of each outcome domain. This article describes the rationale, methods and design of a longitudinal and naturalistic study of subjects with epidemiologically defined first-admission psychosis. Methods: Eligible subjects were recruited from consecutive admissions between January 1990 and December 2009. Between January 2018 and June 2021, we sought to trace, re-contact and re-interview the subjects to assess the clinical course, trajectories of symptoms and functioning, and the different outcomes of psychotic disorders. Since this is a naturalistic study, the research team will not interfere with the subjects’ care and treatment. Predictors include antecedent variables, first-episode characteristics and illness-related variables over the illness course. We assess 8 outcome domains at follow-up: psychopathology, psychosocial functioning, self-rated personal recovery, self-rated quality of life, cognitive performance, neuromotor dysfunction, medical and psychiatric comorbidities and mortality rate. The range of the follow-up period will be 10-31 years with an estimated mean of 20 years. We estimate that more than 50% of the baseline sample will be assessed at follow-up. Discussion: The study design was driven by the increasing need to refine the ability to predict the different clinical outcomes in FEP, and it aims to close current gaps in knowledge, with a broad approach to both the definition of outcomes and their determinants. To the best of our knowledge, this study is one of the few attempting to characterize the very long-term outcome of FEP and the only study addressing 8 major outcome domains. We hope that this study helps to better characterize the long-term outcomes and their determinants, enabling better risk stratification and individually tailored, person-based interventions.